Analysis Of Farmers Carp (Cyprinus Carpio) In The Pond In Janji Lobi Lima Village, Lubuk Barumun Subdistrick, Padang Lawas Districk Of Sumatra Utara Province - Nurul Iman Daulay; Eni Yulinda; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
the research was implemented at april in janji lobi lima village of lubuk barumun subdistrick. The ojektive this result were to analyze production, productivity and farmers carp profits in the pond culture. the result showed that the carp pond cultivation of land 189 m2 producing 745 kg/harvest, productivity 3,93 kg/m2. Total carp cultivation cost Rp 6.815.262,- carp farmer get profit Rp 17.029.791/harvest.Key word: Production, productivity, cost and profits